Pengaruh Iklim Organisasi Dan Komitmen Organisasi Terhadap Kinerja Karyawan PDAM Cabang Kolaka - Suwarto Suwarto; Hendrik Hendrik; Rika Amelia (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine the influence of organizational climate and organizational commitment on employee performance at PDAM Kolaka branch. This research uses a quantitative method approach. Data collection in this research used observation and questionnaires. The population of this study were employees of PDAM Kolaka branch. Meanwhile, the sample in this study amounted to 40 people. Research instrument testing uses validity and reliability tests with SPSS 25.0. The data analysis technique used in this research is instrument model testing (outher model) and structural model testing (Inner model) with Smart PLS 3.0. Based on the research results, it is known that there is a positive and significant influence between the Organizational Climate variable on employee performance as indicated by the T-statistic value of 2.731 and the original sample of 0.369, while the Organizational Commitment variable has a positive and significant influence on employee performance as indicated by the T-statistic value of 3.605 with an original sample value of 0.416.